Contrasting responses to salinity and future ocean acidification in arctic populations of the amphipod Gammarus setosus. (December 2020) - Brown, James; Whiteley, Nia M.; Bailey, Allison M.; Graham, Helen; Hop, Haakon; Rastrick, Samuel P.S.
Abstract: Climate change is leading to alterations in salinity and carbonate chemistry in arctic/sub-arctic marine ecosystems. We examined three nominal populations of the circumpolar arctic/subarctic amphipod, Gammarus setosus, along a salinity gradient in the Kongsfjorden-Krossfjorden area of Svalbard. Field and laboratory experiments assessed physiological (haemolymph osmolality and gill Na + /K + -ATPase activity, NKA) and energetic responses (metabolic rates, MO2, and Cellular Energy Allocation, CEA). In the field, all populations had similar osmregulatory capacities and MO2, but lower-salinity populations had lower CEA. Reduced salinity (S = 23) and elevated p CO2 (~1000 μatm) in the laboratory for one month increased gill NKA activities and reduced CEA in all populations, but increased MO2 in the higher-salinity population. Elevated p CO2 did not interact with salinity and had no effect on NKA activities or CEA, but reduced MO2 in all populations. Reduced CEA in lower-rather than higher-salinity populations may have longer term effects on other energy demanding processes (growth and reproduction). Highlights: Climate change is leading to changes in salinity and p CO2 in arctic/sub-arctic coastal ecosystems. We examined Gammarus setosus at 3 sites along a salinity gradient in the field and laboratory. Reduced salinity had more of an effect than elevated p CO2 by reducing energy budgets. Lower salinities increased ion transporting capacities in the laboratory but not in the field. G. setosus at lower salinity sites have lower energy budgets suggesting impacts on performance.